Remote sensing of wetlands in South America: status and challenges - Kandus, Patricia (2018)
South America has a large proportion of wetlands compared with other continents. While most of these wetlands were conserved in a relatively good condition until a few decades ago, pressures brought about by land use and climate change have threaten their integrity in recent years. The aim of this article is to provide a bibliometric analysis of the available scientific literature relating to the remote sensing of wetlands in South America. From 1960 to 2015, 153 articles were published in 63 different journals, with the number of articles published per year increasing progressively since 1990. This rise is also paralleled by an increase in the contribution of local authors. The most intensively studied regions are the wetland macrosystems of South American mega-rivers: the Amazon and Paraná Rivers, along with the Pantanal at the headwaters of Paraguay River. Few studies spanned more than two countries. The most frequent objectives were mapping, covering all types of wetlands with optical data, and hydrology, focusing on floodplain wetlands with microwave data as the preferred data source. The last decade substantial growth reflects an increase in technological and scientific capacities. Nevertheless, the state of the art regarding the remote sensing of wetlands in South America remains enigmatic. Fundamental questions and guidelines which may contribute to the understanding of the functioning of these ecosystems are yet to be fully defined and there is considerable dispersion in the use of data and remote-sensing approaches.